Spatial nano-scaled organization of heterochromatin in nuclei of endothelial cells after exposure to uremic and dialytic milieu - Bartosova, Maria; Saleem, Arslan; Schäfer, Myriam; Messerschmidt, Gesine; Schmitt, Claus P.; Hausmann, Michael (Nanoscale, 2025)
Cardiovascular disease is frequent in patients with chronic kidney disease (CKD); this risk increases further with peritoneal dialysis (PD), especially when high glucose degradation products (GDP) containing PD fluids (PDF) are used. We studied the spatial organization of the genome orchestrated by heterochromatin rearrangements (fluorescently labelled against H3K9me3 methylation sites) using super-resolution Single Molecule Localization Microscopy (SMLM) and novel combined, mathematical approaches. These were based for geometry and clustering on Ripley statistics, and for topology on persistent homology, persistent imaging and principal component analysis. As a model system, endothelial cells (HUVEC) were exposed to plasma from healthy and CKD individuals and to glucose-based PDF with different buffer and different GDP concentrations. H3K9me3 representing heterochromatin was clustering in endothelial cells. The clusters varied between CKD plasma donors, whereas PDF consistently increased endothelial heterochromatin relaxation and reduced H3K9me3 clustering, with significant differences based on the buffer and GDP content. Bicarbonate PDF with low-GDP concentrations induced high heterochromatin relaxation, i.e., unveiled most H3K9me3 molecules at the lowest level of relative clustering. Persistent homology varied between single and medium exposed cells, but varied less with PDF exposure. High-GDP PDF induced the highest degree of H3K9me3 disarrangement with the GDP 3,4-DGE dose-dependently increasing HC relaxation and lowering clustering to a level below controls. Structural heterochromatin (re-)organization of endothelial cells is variable in response to CKD plasma, while PDF induce major heterochromatin relaxation, depending on the buffer and GDP content, indicating additional chromatin accessibility related changes in genetic activity. Our findings provide a novel base for studying PD biocompatibility and vascular endothelial health.
Gesehen am 15.10.2025